2014
DOI: 10.1259/bjr.20140362
|View full text |Cite
|
Sign up to set email alerts
|

A new variable for SRS plan quality evaluation based on normal tissue sparing: the effect of prescription isodose levels

Abstract: A new variable was proposed based on which normal tissue sparing was quantitatively evaluated, comparing different prescription IDLs in SRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…The results of the optimal IDL for VMAT plans in our study are consistent with the conclusion of the study concerning linac‐based dynamic conformal arc plans, which also indicates that lower IDL plans have lower GI and steeper dose falloff comparing with high IDL plans . Moreover, it is further proposed in our study that a too low IDL (<60%) should be avoided as it may increase the risk of radiation necrosis and also for safety concern.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the optimal IDL for VMAT plans in our study are consistent with the conclusion of the study concerning linac‐based dynamic conformal arc plans, which also indicates that lower IDL plans have lower GI and steeper dose falloff comparing with high IDL plans . Moreover, it is further proposed in our study that a too low IDL (<60%) should be avoided as it may increase the risk of radiation necrosis and also for safety concern.…”
Section: Discussionsupporting
confidence: 90%
“…For CK‐based SRS, Qianyi Xu et al concluded that lower IDL plans (49.6 ± 2.1%) outperform high IDL plans (88.6 ± 1.3%) with lower dose of normal brain tissue and better CI . A new index named dose‐dropping speed was proposed by Q. Zhang et al to evaluate the impact of IDL in linac‐based SRS using non‐coplanar dynamic conformal arcs as well . It is found that the dose‐dropping speed increases with decreasing IDL and reach a plateau around 60–70% IDL.…”
Section: Introductionmentioning
confidence: 99%
“…A recent SRS study on brain lesions had proposed the dose dropping speed concept by fitting the mean dose in multiple rind structures around PTV with a double exponential function of the distance from the PTV surface. 17 An observation made in their study which matched with ours is that a significantly steep dose falloff and better normal tissue sparing was observed in prescribing to 60% -70% isodose lines than in 90% isodose line especially for smaller tumors. While exploring the wider range of 50% -90%, the dose dropping speed was found to increase with decreasing prescription isodose line and plateaus at 60% -70% isodose line.…”
Section: Figure 5 Andsupporting
confidence: 81%
“…Since the dose decreases exponentially (15–17) with the out‐of‐field distance, the basis of our model is an exponential function. In regard to the conclusion of Zang et al, (18) a simple exponential decay function has been selected rather than a double exponential function, shown in Eq. (1).…”
Section: Methodsmentioning
confidence: 99%